Середньовічна лунниця з Малокопанського городища - Калініченко, Віталій; Прохненко, Ігор (Видавництво УжНУ "Говерла", 2020)
The article is devoted to a comprehensive analysis of a significant find, namely lunula, which was discovered during the research of Mala Kopanya hillfort (Zakarpattia oblast, Ukraine). This decoration allows performing a chronological analysis of the studied hillfort. According to A. Dragota's typology, the lunula from the Mala Kopanya is worth classifying as type 7. It is established that lunulas with triple spurs from the base, obviously, are characteristic of the X – first half of the XI century. More precise dating of the lunula from Mala Kopanya according to A. Dragota – 950 – the first half of the XI century. Apparently, according to the specific characteristics of similar lunulas from the Carpathian-Balkan region, the hillfort of Mala Kopanya at this time dates back to the Xth century and continues until the XIth century. It has been established that today lunulas is not often found on the hillforts of the IX-XI centuries, so each find requires a detailed, careful analysis. Typological analysis and chronological attribution of one such ornament found at the Mala Kopanya hillfort is the proposed publication's primary purpose. Correlation of its time range of use with other finds is one of the priority tasks to clarify many contradictory moments in the history of the north-eastern outskirts of the Upper Potyssia in the Middle Ages. Reconstruction of fortifications and the location of a hillfort on a hard-to-reach mountain indicate that the point's protective function was one of the main in its use in the Middle Ages. The hillfort served as a shelter, and its inhabitants settled on the border of mountain and plain zones, near the main microregion's waterway. The fortified point was organized by the Slavic population, which in the late 10th century after the Pechenegs penetrated their territory, they were forced to retreat to the mountains.
The medieval lunula from the Mala Kopanya hillfort
Keywords: середньовіччя; Закарпаття; городище; ювелірні вироби; лунниця; типологія; Middle Ages; Transcarpathia; hillfort; jewelry; lunula; typology